2007
DOI: 10.1051/forest:2006083
|View full text |Cite
|
Sign up to set email alerts
|

Composition, distribution and supposed origin of mineral inclusions in sessile oak wood — consequences for microdensitometrical analysis

Abstract: -SEM and light-microscopical observations, supported by chemical microanalysis with an EDXA system, revealed that light-saturated pixels observed in X-ray negatives of sessile oak (Quercus petraea Liebl.) wood were caused by inorganic deposits present inside multiseriate ray and axial parenchyma cells. Calcium oxalate crystals, silica grains and amorphous granules with varied mineral compositions have been identified. The wood strips of three out of six sampled trees contained measurable amounts of mineral inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Nevertheless, the morphological diversity must be related to the elemental composition because crystalline structures may be modified when other elements become part of the molecules (De Yoreo and Dove, 2004). The Ca concentration in weddellite for the three species was over 80%, almost four times greater than quantities reported for mono-and dihydrated Ca (webmineral, 2014), and greater than the 21.67% of Ca reported in Quercus petraea wood, which is classified as trihydrate (Vansteenkiste et al, 2007). This finding is significant because the soils where the species grow do not have significant quantities of soluble Ca (Bárcenas-Argüello et al, 2010).…”
Section: Elemental Compositionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, the morphological diversity must be related to the elemental composition because crystalline structures may be modified when other elements become part of the molecules (De Yoreo and Dove, 2004). The Ca concentration in weddellite for the three species was over 80%, almost four times greater than quantities reported for mono-and dihydrated Ca (webmineral, 2014), and greater than the 21.67% of Ca reported in Quercus petraea wood, which is classified as trihydrate (Vansteenkiste et al, 2007). This finding is significant because the soils where the species grow do not have significant quantities of soluble Ca (Bárcenas-Argüello et al, 2010).…”
Section: Elemental Compositionmentioning
confidence: 92%
“…Concerning morphology, biogenic minerals frequently differ significantly from inorganic minerals (Lowenstam and Weiner, 1989) and may have different crystal structures when other elements become part of the crystal molecules (De Yoreo and Dove, 2004;Ward, 2005). Biogenic minerals have different forms and hydration states, allowing them to be used as taxonomic or phylogenetic characters (Franceschi and Nakata, 2005;Horner et al, 2009;Lersten and Horner, 2000, 2006, 2008Prychid et al, 2003;Vansteenkiste et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The flecks as measured using the 50-lm traverse increments in Itrax are also similar in size to those previously reported. Smaller calcium crystals were also observed in radiograms of pedunculate oak (Quercus robur, also known as Q. pedunculata) and attributed to calcium oxalate on the basis of crystal shape (Vansteenkiste et al, 2007). Calcium oxalate is one of the most common biominerals in forest vegetation and forest soils, produced by both plants and fungi (Verrechia et al, 2006;Smith et al, 2009) and observed in poplar (Todeschini et al, 2011).…”
Section: Biomineralizationmentioning
confidence: 99%
“…Since primary cell walls have higher concentrations of pectins than secondary walls (Sarkar et al 2009 ), cell types with thick secondary walls such as fibers should have a lower proportion of pectins and cations binding to these than thin-walled parenchyma cells. Mineral inclusions in wood have high concentrations of specific elements, they are not distributed uniformly and can be seen in micro-density measurements (Vansteenkiste et al 2007 ) and chemically analyzed by energy-dispersive X-ray fluorescence (Smith et al 2014 ). The concentration of nutrients essential for the functioning of living cells will depend on the proportion of living (parenchyma) cells in wood, which often decreases from the cambium onwards and is zero in heartwood.…”
Section: Introductionmentioning
confidence: 99%